Theory and method in higher education research. volume 10 - Huisman, Jeroen; Tight, Malcolm (Emerald Publishing Limited, 2024)
Higher education research is a developing field internationally, which is attracting more and more researchers from a great variety of disciplinary backgrounds within and beyond higher education institutions. As such, it is an arena within which a wide range of theories, methods and methodologies are being applied. This volume of Theory and Method in Higher Education Research explores theories such as the use of the "landscape" metaphor, a holistic framework for analysing student behaviour, gendered career choices in STEM, and Bourdieu and posthumanist theorizing. Methodological contributions cover measuring student departure, the use and pitfalls of replication studies, and reflections on autoethnography in higher education research. Combining both strands, the relevance of the rhizome perspective in higher education research is explored in depth. The international authorship stemming from the UK, Germany, Belgium, the Netherlands, Austria, Norway and Italy provide rich and varied forum for higher education discussions around issues of theory and method.
Includes index.
Keywords: Education, Higher.; Education -- Schools -- Levels -- Higher.; Higher education, tertiary education.; elektronické knihy; electronic books